The Influence of Ways of Organizing Learning Interactions on the Development of Communicative and Reflexive Abilities of Children 6-10 Years Old - Rubtsov V.V; Ulanovskaya I.M (Moscow State University of Psychology and Education, 2022)
The features of the development of communicative and reflexive abilities of children aged 6-10 years, depending on the ways of organizing educational interactions, are discussed. Basic social competencies defined by the requirements of the current Federal State Educational Standard of Primary General Education are considered as indicators of the development of abilities in the learning environment. Based on the selected indicators, a variant of the "Puzzle" diagnostic method has been developed, which allows to study the relationship between the development of social competencies in younger schoolchildren, and the joint way they perform while solving experimental problems. A comparative analysis of students' social competencies allows to prove the influence of ways of organizing educational interactions on the development of communicative and reflexive abilities of primary school children.